Learning Discussing the Epic Novels (Eurasian Journal of Learning and Academic Teaching, 2022)
Methods of artistic representation are modified by the writer, they are combined and synthesized with each other when necessary, and have a scientific-theoretical and practical significance. Thus, by analyzing works of art in the minds of students, we form universal human feelings and values, restore the true history of the people, and bring up an aesthetic feeling. We create the basis for the formation of speech cults and breaking of linguistic wealth.